2016
DOI: 10.1002/jmv.24481
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic proinflammatory chemokines levels are tricky markers to monitoring HTLV-1 carriers

Abstract: The human T-cell leukemia virus type 1 (HTLV-1) is present throughout the world and is associated with HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and other inflammatory conditions. The pathogenesis of HAM/TSP involves a chronic inflammatory response in central nervous system (CNS), with the presence of HTLV-1 infected cells and HTLV-1-specific CD8+ lymphocytes. Chemokines may have a role in the infiltration of these cells into the CNS. In this context, the present study analyzed the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…However, the CD4 T cell responses to HTLV‐1, the predominant subset of lymphocytes infiltrating the CNS, are important for activating CTLs, monocytes, and B cells early in the development and progression of HAM/TSP. These infected CD4 + T cells spontaneously secrete proinflammatory cytokines and chemokines in the CNS and the blood, such as IFN‐γ, TNF‐α, and GM‐CSF, and chemokines such as IL‐8, monocyte chemoattractant protein‐1 (MCP‐1 or CCL2), macrophage inflammatory protein 1 alpha (MIP‐1a or CCL3) and beta (MIP‐1ß or CCL4), CCL2 and CCL5 . Therefore, an increase in HTLV‐1‐infected CD4+ T cells, which consequently heightens transmigrating activity to the spinal cord, might play a pivotal role in triggering inflammatory reactions and inducing HAM/TSP development…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CD4 T cell responses to HTLV‐1, the predominant subset of lymphocytes infiltrating the CNS, are important for activating CTLs, monocytes, and B cells early in the development and progression of HAM/TSP. These infected CD4 + T cells spontaneously secrete proinflammatory cytokines and chemokines in the CNS and the blood, such as IFN‐γ, TNF‐α, and GM‐CSF, and chemokines such as IL‐8, monocyte chemoattractant protein‐1 (MCP‐1 or CCL2), macrophage inflammatory protein 1 alpha (MIP‐1a or CCL3) and beta (MIP‐1ß or CCL4), CCL2 and CCL5 . Therefore, an increase in HTLV‐1‐infected CD4+ T cells, which consequently heightens transmigrating activity to the spinal cord, might play a pivotal role in triggering inflammatory reactions and inducing HAM/TSP development…”
Section: Discussionmentioning
confidence: 99%
“…Healthy controls, in this study, were a homogenous population compared to HAM/TSP patients and HTLV‐1 carriers and there were not confounding variables to affects the significant differences in CXCR3 expression. It is more likely the some factors such as proviral load, clinical status of HAM/TSP patients, treatment of the patients with immmunomodulatory drugs, duration of the disease and infection, and genetic background of the HTLV‐1 infected individuals may influence in creating controversial results regarding the association of chemokines and their receptors in HTLV‐1 infection …”
Section: Discussionmentioning
confidence: 99%
“…CXCL9 and CXCL10 are presented in high levels in serum and CSF of patients with HAM/TSP and contribute to the pathogenesis of HAM/TSP Guerra et al, 2018). Chaves et al showed that the plasma levels of CXCL8 and CXCL9 were greater in HAM/TSP patients compared to carriers (Chaves et al, 2016). Moreover, a correlation was observed between plasma levels of CXCL8, CXCL9, and CXCL10 and proviral load, in which the HTLV-1 infected individuals with higher proviral loads had increased plasma levels of these chemokines (Chaves et al, 2016).…”
Section: Cxcl9 and Cxcl10mentioning
confidence: 99%
“…Chaves et al showed that the plasma levels of CXCL8 and CXCL9 were greater in HAM/TSP patients compared to carriers (Chaves et al, 2016). Moreover, a correlation was observed between plasma levels of CXCL8, CXCL9, and CXCL10 and proviral load, in which the HTLV-1 infected individuals with higher proviral loads had increased plasma levels of these chemokines (Chaves et al, 2016). CXCL10 in the CSF, as indicators of CNS inflammation, correlate with disease progression and has been suggested as a candidate for the prognosis of HAM/TSP development (Guerreiro et al, 2006;Sato et al, 2013;Lima et al, 2017).…”
Section: Cxcl9 and Cxcl10mentioning
confidence: 99%
See 1 more Smart Citation